2020
DOI: 10.1111/jir.12764
|View full text |Cite
|
Sign up to set email alerts
|

Family‐based social capital of emerging adults with and without mild intellectual disability

Abstract: Background Family is recognised as an important context for the self‐development of young adults in emerging adulthood, although very little research has addressed the perspective of young people with intellectual disability about their families by using self‐report. This study examined how emerging adults with mild intellectual disability define their family support networks, compared with definitions of students without intellectual disability, within a social capital theoretical framework. Methods Fifty‐thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…This is consistent with previous research, which has shown that parents can play a key role in building the decision‐making capacity and autonomy of their offspring with intellectual disabilities (Van Asselt‐Goverts et al, 2013 ). However, in line with previous research, the current study also shows that parents may find it difficult to know what is best for their offspring, and to balance their need to protect their offspring with respect for their offspring's own wishes (Curryer et al, 2019 ; Giesbers et al, 2020 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is consistent with previous research, which has shown that parents can play a key role in building the decision‐making capacity and autonomy of their offspring with intellectual disabilities (Van Asselt‐Goverts et al, 2013 ). However, in line with previous research, the current study also shows that parents may find it difficult to know what is best for their offspring, and to balance their need to protect their offspring with respect for their offspring's own wishes (Curryer et al, 2019 ; Giesbers et al, 2020 ).…”
Section: Discussionsupporting
confidence: 85%
“…However, as with all offspring, as they grow up and become more autonomous, their wishes and needs may change. For people with intellectual disabilities, who remain reliant on their families, this may become challenging for the parents and for the person with intellectual disabilities (Curryer et al, 2019 ; Giesbers et al, 2020 ). To ensure good quality of life for all family members, including the person with intellectual disabilities, it is important to support the family as a system (Hastings, 2016 ; Seligman & Darling, 2009 ), and to understand the needs of parents.…”
Section: Introductionmentioning
confidence: 99%
“…A SI programme which adopted a "general differences position" would therefore treat interns as different from others and thus in need of a separate environment to those without learning disabilities. The presence of the "unique differences" position (Norwich and Lewis, 2007) in the "interpersonal" relationships established between colleagues and interns points therefore to the broader, deeper "organisational" (Simplican et al, 2015) reciprocal relationships (depth of social inclusion) (Giesbers et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this finding, it was found that in South Africa fathers left their families, avoiding being associated with children with disability [ 21 ]. The literature asserts that children with ID have fewer relationships with those nuclear family members who expose them to unsafe home environments [ 31 ]. The study highlights less support of mothers by their spouses who were always absent either due to work or failed relationships, leaving all parental responsibilities to mothers.…”
Section: Discussionmentioning
confidence: 99%